The three-dimensional XY universality class: a high precision Monte Carlo estimate of the universal amplitude ratio A+/A- - Hasenbusch, Martin (Journal of statistical mechanics: theory and experiment, 2006)
We simulate the improved three-dimensional two-component ϕ4 model on the simple cubic lattice in the low and the high temperature phase for reduced temperatures down to |T − Tc|/Tc ≈ 0.0017 on lattices of size up to 3503. Our new results for the internal energy and the specific heat are combined with the accurate estimates of βc and data for the internal energy and the specific heat at βc recently obtained in Campostrini et al (2006 Preprint cond-mat/0605083). We find Rα = (1 − A+/A−)/α = 4.01(5), where α is the critical exponent of the specific heat and A ± is the amplitude of the specific heat in the high and the low temperature phase, respectively.